Rapidly Expanding Glacial Lakes in Nepal Himalaya - Khadka, Nitesh; Ghimire, Shravan Kumar; Sharma, Shankar; Hamal, Kalpana (Jalawaayu, 2022)
The retreat and shrinkage of glaciers due to climate change are the causes for the formation and expansion of glacial lakes in the Himalayas. This study presents the rapidly expanding glacial lakes in Nepal Himalayas between 1988 and 2018 based on the published glacial lake inventories produced from Landsat imageries (30 m). Glacier-fed end moraine-dammed glacial lakes whose surface area was?0.1 km2 in 2018 with an expansion rate of more than 30% in 1988-2018 were regarded as rapidly expanding glacial lakes. The results show that 19 rapidly expanding glacial lakes are heterogeneously distributed in different sub-basins of Nepal. Among the sub-basins, Dudh Koshi sub-basin has a maximum (5) number of rapidly expanding glacial lakes. The total surface area of these 19 glacial lakes expanded by ~133%, from 4.12±0.61 km2 in 1988 to 9.62±1.04 km2 in 2018. Regular monitoring of rapidly expanding glacial lakes is required because the rapid expansion heightens the risk of GLOF by developing more potential flood volume and the expanding lakes can reach sites of possible avalanches.